NRS20: Combined Back and Leg Pain Score. Issue 17 (1st September 2018) - Cawley, Derek T.; Larrieu, Daniel; Fujishiro, Takashi; Kieser, David; Boissiere, Louis; Acaroglu, Emre; Alanay, Ahmet; Kleinstück, Frank; Pellisé, Ferran; Pérez-Grueso, Francisco Sánchez; Vital, Jean-Marc; Gille, Olivier; et al.
Abstract : Study Design: Multicenter, prospective study of consecutive adult spinal deformity (ASD) patients. Objective: To evaluate back and leg pain as a combined score in ASD and compare their relative and cumulative correlations with health-related quality of life (HRQOL) and sagittal parameters. Summary of Background Data: Pain and disability are commonly reported in patients with ASD. This can affect their back, their legs or both. ASD-associated pain has been correlated with numerous HRQOL scores and radiological parameters. Methods: Preoperative pain intensity was assessed with a Numerical Rating Scale (NRS) for individual back and leg pain as well as a combined score, NRS20 (0–20, back plus leg pain). This yielded a range of static measures in all patients with ASD with differing burdens of disease. Linear regression analysis was performed to calculate the correlation between pain and HRQOL scores (Scoliosis Research Society 22, 36-Item Short Form Health Survey Physical Component Summary, 36-Item Short Form Health Survey Mental Component Summary, Core Outcome Measures Index, and Oswestry Disability Index), and radiological spinopelvic parameters (sagittal and coronal planes). Results: A total of 1309 patients were included in this study. A combined score (NRS20) was better correlated with HRQOL ( P  < 0.01 for all) and sagittal parameters ( P  < 0.01 for all) than individual back or leg pain scores. Evaluation of the relative contributions of back and leg pain demonstrate a higher correlation with HRQOL scores for back pain and a higher correlation with sagittal parameters for leg pain. The distribution of NRS20 pain scores demonstrated three clear patterns of pain: back pain only, moderate back pain with varying mild-moderate leg pain, and severe equivalent back and leg pain. Similar values were noted for nonoperative and operative patients. Conclusion: The distribution and intensity of pain and its correlations with clinical and radiological parameters provide insight into the pathogenesis of ASD. A combined score has a simple yet valuable contribution to the assessment of symptoms in ASD. Level of Evidence: 3